The Role of The Administrators in Increasing The Motivation to Learn The Yellow Book in Students at The Al-Ihya Islamic Boarding School ‘Ulumaddin Kesugihan Cilacap - Ulin Nuha, Muhammad (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This study aims to determine the role of administrators in increasing the motivation to learn the yellow book of students at the Al Ihya Islamic Boarding School 'Ulumaddin Kesugihan Cilacap. This research is a type of field research (field research). The approach of this research is qualitative research. With the target of research on the motivation to learn the yellow book of students. Therefore, the subject of this research includes caregivers, administrators, and PPAI students. The method used in obtaining data that can support research, researchers use the method of observation, documentation, and interviews. The steps in data analysis techniques in this study include data reduction, data presentation, and verification and drawing conclusions. From the results of the analysis, the authors can conclude that the management plays a role in increasing the motivation to learn the yellow book of students through guiding the students, explaining everything that is studied in the yellow book and providing motivation both in the recitation process and by exemplifying good behavior in everyday life. Of course, this shows the role of the board in motivating the students to learn the yellow book which then has an influence on the motivation of the students in learning the yellow book.